2021
DOI: 10.3389/fmolb.2021.646524
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Residue-Specific Binding Free Energies of Androgen Receptor to Ligands

Abstract: Androgen receptor (AR) is an important therapeutic target for the treatment of diseases such as prostate cancer, hypogonadism, muscle wasting, etc. In this study, the complex structures of the AR ligand-binding domain (LBD) with fifteen ligands were analyzed by molecular dynamics simulations combined with the alanine-scanning-interaction-entropy method (ASIE). The quantitative free energy contributions of the pocket residues were obtained and hotspot residues are quantitatively identified. Our calculation show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Our simulations have shown that residues involved in the binding of those small molecules (e.g., T603, K610, R611) sampled a series of different configurational states through the nanoseconds to microseconds timescale, which is likely to contribute to the relatively low affinities of the compound (e.g., K i within µM range reported for pyrvinium) [ 22 ]. Challenges of direct DBD targeting rendered the LBD a more attractive binding site for small molecules, given its reported allosteric sites and highly conserved orthosteric pocket [ 24 , 25 , 26 , 27 ]. However, AR mutants lacking LBD (e.g., ARV7; exon 4 deletion), which remain functional receptors yet insensitive to inhibitors targeting LBD, are the leading cause of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Our simulations have shown that residues involved in the binding of those small molecules (e.g., T603, K610, R611) sampled a series of different configurational states through the nanoseconds to microseconds timescale, which is likely to contribute to the relatively low affinities of the compound (e.g., K i within µM range reported for pyrvinium) [ 22 ]. Challenges of direct DBD targeting rendered the LBD a more attractive binding site for small molecules, given its reported allosteric sites and highly conserved orthosteric pocket [ 24 , 25 , 26 , 27 ]. However, AR mutants lacking LBD (e.g., ARV7; exon 4 deletion), which remain functional receptors yet insensitive to inhibitors targeting LBD, are the leading cause of drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…MM/GBSA is a common method for calculating enthalpic contribution. 76–81 Its basic principle is the conversion of the enthalpy change into the sum of the gas-phase free energy (Δ G gas ) and solvation free energy (Δ G sol ):Δ H = Δ G gas + Δ G sol …”
Section: Methodsmentioning
confidence: 99%